Strengthening Character Education through Student-Centered Learning in Secondary Schools Vol 2 no 1 - ahmad (Innovative Pedagogy and Education Studies, 2025)
This study examines the role of student-centered learning in strengthening character education in secondary schools. Character education is a crucial component in developing students’ moral values, responsibility, and social awareness. Student-centered learning emphasizes active participation, critical thinking, collaboration, and learner autonomy, which provide opportunities for students to internalize positive character values through meaningful learning experiences. This research employs a qualitative descriptive approach, with data collected through classroom observations, interviews with teachers and students, and documentation analysis. The findings reveal that student-centered learning effectively promotes character development, particularly in aspects of responsibility, discipline, cooperation, and respect for others. However, challenges such as limited teacher readiness and classroom management constraints remain obstacles to optimal implementation. Overall, student-centered learning contributes positively to the strengthening of character education in secondary schools.